Fulfillment of Child Support Rights After Divorce by a Convicted Father - Anggraeni, Dinda Restya; Sulastri, Sulastri (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Children are a mandate and gift from God who naturally have dignity and honor as human beings. On that basis, children have the right to receive full protection, especially regarding the protection of their basic rights. According to Government Regulation (PP) Article 1 No. 59 of 2019,